Seroprevalence of Salmonella and Mycoplasma infection in backyard chickens in the state of Entre Ríos in Argentina - Xavier, J. (2011)
The present work was conducted to study the seroprevalence of Salmonella, Mycoplasma gallisepticum (MG), and Mycoplasma synoviae (MS) infection in backyard chickens located in Entre Ríos, Argentina, over 3 periods of time. A total of 2,441 sera samples were collected from backyard chickens belonging to 256 family farms in 16 counties in the state of Entre Ríos from January to May 2003 (first period), December 2004 to April 2005 (second period), and October 2006 to May 2007 (third period). The prevalence of family farms testing seropositive for Salmonella averaged 23.9, 15.9, and 28.6% during the first, second, and third period, respectively. The highest prevalence of Salmonella-seropositive farms recorded (66.7%) was on farms from Concordia county, and the lowest prevalence (0%) was on farms from La Paz county. In contrast, the prevalence of family farms seropositive for MG averaged 32.8, 55.1, and 76.2% during the first, second, and third periods, respectively. The highest prevalence of MG-seropositive farms (100%) was found in the counties of Victoria and Tala, and the lowest prevalence (8.7%) was found on farms on Colón county. The prevalence of family farms seropositive for MS averaged 68.6 and 100% during the first and second periods, respectively. The highest prevalence of MS-seropositive farms (100%) was on farms in 85% of the counties tested, and the lowest prevalence (21.7%) was on farms from Colón county. Salmonella, MG, and MS infection are present at high levels in backyard chicken farms, and this presents a high risk to commercial poultry production in Entre Ríos, the state with the highest chicken population and density in Argentina.